Preparation method of mesoporous ultra-stable aluminum oxide

Mesoporous superstable alumina was prepared by the double-alumina method, the crystallization pH and temperature were controlled, and sodium silicate and hexamethyldisilazane were added, which solved the problem of pore structure collapse and specific surface area reduction of alumina materials in high-temperature hydrothermal environments, and achieved efficient heavy oil treatment and high-temperature stability of the catalyst.

CN120172439AActive Publication Date: 2025-06-20LINQU HENGHUI NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510645932.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-06-20
Estimated Expiration
2045-05-20

AI Technical Summary

Technical Problem

The existing alumina materials have problems of pore structure collapse and specific surface area reduction in high temperature hydrothermal environments, resulting in a decrease in the heavy oil treatment capacity of the catalyst.

Method used

Mesoporous superstable alumina was prepared by the double-alumina method. By controlling the crystallization pH value and temperature, combined with the addition of sodium silicate and hexamethyldisilazane, the pore structure and high temperature stability of the alumina powder were modified.

Benefits of technology

The high hydrothermal stability and pore structure of alumina materials are achieved, and the heavy oil treatment capacity and high temperature stability of the catalyst are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst carrier materials, and particularly relates to a preparation method of mesoporous ultra-stable aluminum oxide. Pseudo-boehmite is prepared by adopting a double-aluminum method, alumina powder is obtained after roasting, a layer of fibrous pseudo-boehmite is prepared in the pore structure of the alumina powder, and the pore structure and the specific surface area of mesoporous super-stable alumina are controlled by controlling the crystallization pH value and the crystallization temperature in the reaction process. Sodium silicate and hexamethyldisilazane are added in the preparation process, so that the high-temperature stability of the mesoporous super-stable aluminum oxide is effectively improved, and the mesoporous super-stable aluminum oxide still has good specific surface area and pore volume under a hydrothermal condition. The mesoporous stable alumina is prepared by taking sodium metaaluminate and aluminum sulfate as main raw materials, and an organic solvent is not added as a template agent in the preparation process, so that volatilization of the organic solvent is effectively avoided, and the mesoporous stable alumina is green and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst carrier materials, and particularly relates to a preparation method of mesoporous ultra-stable alumina. Background Art

[0002] In modern petrochemical and chemical industries, more than 90% of chemical reactions are realized through catalysts. Among the solid catalyst carriers used in oil refining and petrochemical industries, the proportion of activated alumina carriers is about 57%. Due to the continuous expansion of the application of catalysts in the chemical and environmental protection fields, higher requirements are put forward for the performance of activated alumina powder, and the preparation method is closely related to the performance.

[0003] During the catalytic cracking reaction process, the oil and gas adsorbed on the surface of the spent catalyst need to be purged with high-temperature steam in the stripping stage. In high-temperature steam, the specific surface area and pore volume of the cracking catalyst will both decrease, and the reaction performance of the catalyst will decrease. Especially, traditional alumina matrices do not have high hydrothermal stability and are prone to phase transformation and pore structure collapse in a high-temperature steam atmosphere, which will cause a significant reduction in the heavy oil treatment capacity of the regenerated catalyst. Therefore, making alumina have high hydrothermal stability and maintaining a highly porous structure of the alumina matrix in a hydrothermal environment is an important guarantee for improving the heavy oil treatment capacity of cracking catalysts. In addition, compared with macroporous alumina powder, alumina powder with a mesoporous structure has a more uniform pore size distribution although its specific surface area may be relatively small, which is beneficial to the adsorption of substances and the occurrence of catalytic reactions, and is an ideal carrier material for catalysts.

[0004] The Chinese patent application document with the publication number CN115594207A discloses a macroporous high-specific-surface-area boehmite and its preparation method. The specific preparation method is as follows: (1) React sodium hydroxide, aluminum hydroxide and water to obtain a sodium aluminate solution; (2) Dissolve aluminum sulfate solid to prepare an aluminum sulfate solution, mix the aluminum sulfate solution with the sodium aluminate solution, and perform crystallization to obtain a slurry; (3) Filter the slurry to obtain a filter cake and a filtrate; (4) Wash and dry the filter cake in sequence to obtain boehmite; wherein, the filtrate in (3) is returned to the aluminum sulfate solution for dissolving aluminum sulfate solid. This method uses the filtrate containing sodium sulfate for the preparation of the aluminum sulfate solution, which can make the obtained boehmite have a larger specific surface area and pore volume. However, the crystallization temperature in step (2) is 80-140°C, and the pH value is 8-10. Under these conditions, the boehmite obtained will undergo phase transformation and pore structure collapse at high temperature, resulting in pore structure changes and a decrease in specific surface area, and poor high-temperature stability, which will affect the reaction performance of the catalyst.

[0005] It can be seen that the main problems faced in the development of alumina are the adjustment of the pore volume and specific surface area of the material and the improvement of the high-temperature stability of the alumina material. How to greenly and low-costly synthesize stable alumina with a mesoporous structure has become an urgent problem for researchers to solve. Summary of the Invention

[0006] In order to solve the technical problems of small pore volume and specific surface area of alumina materials and poor high-temperature stability of alumina materials in the prior art, the present invention provides a method for preparing mesoporous ultra-stable alumina.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows: A method for preparing mesoporous ultra-stable alumina, comprising the following steps: S1: Mix aluminum hydroxide powder and sodium hydroxide solution evenly, react for 5-6 h to obtain sodium aluminate solution; S2: Mix a part of the sodium aluminate solution prepared in step S1 with aluminum sulfate solution, stir and heat up, add sodium aluminate solution to control the pH value of the reaction system to 7.8-8.3 until the reaction is completed, continue to heat up for crystallization reaction, then add sodium silicate, continue to react, stand and cool, filter, wash, dry, and grind to obtain a powdery material; S3: Calcinate the powdery material obtained in step S2, and obtain modified alumina powder after cooling; S4: Add the modified alumina powder and hexamethyldisilazane prepared in step S3 to aluminum sulfate solution, heat up, and dropwise add the sodium aluminate solution prepared in step S1 under stirring, add sodium carbonate to control the pH value of the reaction system to 9.7-10.0 until the reaction is completed, continue to heat up for crystallization reaction, cool, filter, wash, dry, and grind to obtain mesoporous ultra-stable alumina.

[0008] The present invention uses a double-aluminum method to prepare pseudo-boehmite, and controls the pore structure and specific surface area of pseudo-boehmite by controlling the crystallization pH value and crystallization temperature during the reaction process. In step S2 of this preparation method, the crystallization pH value is controlled to be 7.8 - 8.3. Within this pH value range, the prepared pseudo-boehmite has a large specific surface area and pore volume. After the crystallization reaction is completed, the addition of sodium silicate can perform silicon modification on the prepared pseudo-boehmite. It is found that adding a small amount of silicate ions can be adsorbed on the surface of pseudo-boehmite. During the calcination process, silicon ions will occupy the alumina tetrahedral vacancies, reducing the total vacancies, thereby inhibiting the lattice vibration and phase transformation of alumina at high temperatures, and thus improving the high-temperature stability of alumina and effectively avoiding the reduction of the specific surface area of alumina during calcination. In addition, the present invention also prepares secondary pseudo-boehmite on the surface of the modified alumina powder obtained after calcination, and controls the crystallization pH value of pseudo-boehmite to be 9.7 - 10, so that the secondary-generated pseudo-boehmite has a fibrous morphology. The fibrous-morphology secondary pseudo-boehmite plays a supporting role in the pore diameter of the modified alumina powder, making the prepared mesoporous ultra-stable alumina have a relatively stable pore structure. At the same time, hexamethyldisilazane is added during the preparation process of secondary pseudo-boehmite. Hexamethyldisilazane can introduce Si-CH3 groups on the surface of alumina particles, which will turn into SiO2 particles at high temperatures and can inhibit the phase transformation of alumina, thereby enhancing the high-temperature stability of alumina.

[0009] Further, in step S1, the molar ratio of sodium hydroxide in the aluminum hydroxide powder and sodium hydroxide solution is 1:3.2 - 3.5; the concentration of the sodium hydroxide solution is 3.5 - 4 mol / L.

[0010] Further, in step S1, the temperature of the reaction is 125 - 130 °C, and the pressure of the reaction is 0.3 - 0.4 MPa.

[0011] Further, in step S2, the volume ratio of the sodium aluminate solution to the aluminum sulfate solution after mixing is 1.2 - 1.5:1; the concentration of the aluminum sulfate solution is 0.2 - 0.4 mol / L.

[0012] Further, in step S2, the temperature of stirring and heating up is 55 - 60 °C, and the time for continuous reaction is 2 - 2.5 h.

[0013] Further, in step S2, the temperature of the crystallization reaction is 85 - 95 °C, and the time of the crystallization reaction is 24 - 30 h.

[0014] The temperature of the crystallization reaction has a great influence on the pore size distribution of pseudo-boehmite. The higher the temperature, the higher the crystallinity of pseudo-boehmite, and the pore size will also increase. However, at high temperatures, the crystallinity and orderliness of pseudo-boehmite will decrease, resulting in an uneven distribution of the pore structure. The crystallization reaction temperature in step S2 of the present invention is selected to be 85-95 °C. The pseudo-boehmite prepared within this temperature range not only has a larger pore size, but also has a moderate grain size and a uniform pore size distribution.

[0015] Further, the molar mass of sodium silicate in step S2 is 0.5%-0.8% of the total molar mass of aluminum in the sodium aluminate solution and the aluminum sulfate solution.

[0016] In the present invention, the modification of pseudo-boehmite by sodium silicate is controlled by controlling the molar ratio of sodium silicate to aluminum in the reaction system. Adding a small amount of sodium silicate can effectively increase the specific surface area and pore volume of pseudo-boehmite. This is because the sulfate radicals on the surface of pseudo-boehmite desorb at high temperatures, while the silicate radicals adsorb on the surface of pseudo-boehmite, inhibiting the growth of pseudo-boehmite grains and increasing the specific surface area and pore volume of pseudo-boehmite. However, when an excessive amount of sodium silicate is incorporated, during the calcination process, the excessive silica generated will block the pore structure of alumina, resulting in a decrease in the specific surface area and pore volume.

[0017] Further, the calcination temperature in step S3 is 820-830 °C, the calcination time is 4-5 h, and the heating rate of calcination is 20-30 °C / min; the cooling rate is 40-50 °C / min.

[0018] Research has found that the calcination temperature of pseudo-boehmite will affect the pore size structure of the prepared alumina. After low-temperature calcination, both the specific surface area and pore volume of alumina will decrease significantly. This is due to the continuous growth of pseudo-boehmite grains during low-temperature calcination, resulting in an increase in grain size. High-temperature calcination will cause the pore structure of alumina to collapse or be blocked, resulting in a decrease in the specific surface area. The calcination temperature selected in the present invention is 820-830 °C. When calcined within this temperature range, the specific surface area of the prepared alumina increases slightly, and the pore volume and pore size change little. This is because only a small amount of pseudo-boehmite undergoes a polymorphic transformation within this temperature range, generating boehmite, and the pitting corrosion of the alumina phase caused by the migration of aluminum atoms to the boehmite results in a slight increase in the specific surface area.

[0019] Further, the volume ratio of the aluminum sulfate solution to the sodium aluminate solution in step S4 is 1:1.2-1.5; the concentration of the aluminum sulfate solution is 0.2-0.4 mol / L.

[0020] Further, the mass ratio of the modified alumina powder to hexamethyldisilazane in step S4 is 10-13:1; the mass ratio of the modified alumina powder to sodium aluminate in the sodium aluminate solution is 7-10:2-3.

[0021] Further, the temperature for the temperature increase in step S4 is 50 - 55 °C.

[0022] Further, the temperature of the crystallization reaction in step S4 is 140 - 150 °C, and the time of the crystallization reaction is 20 - 24 h.

[0023] The present invention adjusts the growth degree of fibrous pseudoboehmite in the pore channels of modified alumina powder by regulating the crystallization reaction temperature of secondary pseudoboehmite. The higher the temperature and the longer the crystallization time, but the pore channels of pseudoboehmite itself will also be damaged under hydrothermal conditions. Therefore, it is necessary to strictly control the growth of fibrous pseudoboehmite in the alumina pore channels.

[0024] Compared with the prior art, the preparation method of mesoporous stable alumina provided by the present invention has the following technical advantages: (1) The present invention uses the double-aluminum method to prepare pseudoboehmite, and after calcination, alumina powder is obtained, and a layer of fibrous pseudoboehmite is prepared in the pore structure of the alumina powder. The pore structure and specific surface area of mesoporous ultra-stable alumina are controlled by controlling the crystallization pH value and crystallization temperature in the reaction process; (2) Sodium silicate and hexamethyldisilazane are added in the preparation process of the present invention, effectively improving the high-temperature stability of mesoporous ultra-stable alumina, so that it still has good specific surface area and pore volume under hydrothermal conditions; (3) Mesoporous stable alumina is prepared from sodium aluminate and aluminum sulfate as the main raw materials in the present invention. No organic solvent is added as a template agent in the preparation process, effectively avoiding the volatilization of organic solvents, which is green and environmentally friendly. Specific Embodiments

[0025] The following will be further described in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications according to the basic idea of the present invention, but as long as they do not depart from the basic idea of the present invention, they are within the scope of the present invention.

[0026] Example 1 A preparation method of mesoporous ultra-stable alumina includes the following steps: S1: Mix aluminum hydroxide powder and a sodium hydroxide solution with a concentration of 3.5 mol / L evenly (the molar ratio of aluminum hydroxide powder to sodium hydroxide in the sodium hydroxide solution is 1:3.2), pressurize to 0.3 MPa, heat up to 125 °C, and react for 6 h to obtain a sodium aluminate solution; S2: Mix the sodium aluminate solution prepared in part of step S1 with the aluminum sulfate solution with a concentration of 0.2 mol / L at a volume ratio of 1.2:1, stir and heat up to 55 °C, add the sodium aluminate solution to control the pH value of the reaction system to 7.8 until the reaction is complete, continue to heat up to 85 °C, carry out crystallization reaction for 24 h, then add sodium silicate (the molar mass of sodium silicate is 0.5% of the total molar mass of aluminum in the sodium aluminate solution and the aluminum sulfate solution), continue to react for 2 h, let it stand and cool, filter, wash with deionized water until there is no sulfate ion in the washing liquid, dry, grind, and obtain a powdery material; S3: Heat the powdery material obtained in step S2 to 820 °C at a rate of 20 °C / min and calcine for 5 h, then cool it to 25 °C at a cooling rate of 40 °C / min to obtain modified alumina powder; S4: Add the modified alumina powder prepared in step S3 and hexamethyldisilazane to the aluminum sulfate solution with a concentration of 0.2 mol / L at a mass ratio of 10:1, heat up to 50 °C, and dropwise add the sodium aluminate solution prepared in step S1 (the volume ratio of the sodium aluminate solution to the aluminum sulfate solution is 1.2:1, and the mass ratio of the modified alumina powder to sodium aluminate in the sodium aluminate solution is 7:2) under stirring, add sodium carbonate to control the pH value of the reaction system to 9.7 until the reaction is complete, continue to heat up to 140 °C, carry out crystallization reaction for 20 h, cool, filter, wash, dry, and grind to obtain mesoporous ultrastable alumina.

[0027] Example 2 A preparation method of mesoporous ultrastable alumina, comprising the following steps: S1: Mix aluminum hydroxide powder and a sodium hydroxide solution with a concentration of 4 mol / L evenly (the molar ratio of aluminum hydroxide powder to sodium hydroxide in the sodium hydroxide solution is 1:3.5), pressurize to 0.4 MPa, heat up to 130 °C, and react for 5 h to prepare a sodium aluminate solution; S2: Mix part of the sodium aluminate solution prepared in step S1 with the aluminum sulfate solution with a concentration of 0.4 mol / L at a volume ratio of 1.5:1, stir and heat up to 60 °C, add the sodium aluminate solution to control the pH value of the reaction system to 8.3 until the reaction is complete, continue to heat up to 95 °C, carry out crystallization reaction for 30 h, then add sodium silicate (the molar mass of sodium silicate is 0.8% of the total molar mass of aluminum in the sodium aluminate solution and the aluminum sulfate solution), continue to react for 2.5 h, let it stand and cool, filter, wash with deionized water until there is no sulfate ion in the washing liquid, dry, grind, and obtain a powdery material; S3: Heat the powdery material obtained in step S2 to 830 °C at a rate of 30 °C / min and calcine for 4 h, then cool it to 25 °C at a cooling rate of 50 °C / min to obtain modified alumina powder; S4: Add the modified alumina powder prepared in step S3 and hexamethyldisilazane to an aluminum sulfate solution with a concentration of 0.4 mol / L at a mass ratio of 13:1, heat up to 55 °C, and dropwise add the sodium aluminate solution prepared in step S1 (the volume ratio of the sodium aluminate solution to the aluminum sulfate solution is 1.5:1, and the mass ratio of the modified alumina powder to sodium aluminate in the sodium aluminate solution is 10:3) under stirring. Add sodium carbonate to control the pH value of the reaction system to 10.0 until the reaction is complete, continue to heat up to 150 °C, carry out the crystallization reaction for 24 h, cool, filter, wash, dry, and grind to obtain mesoporous ultrastable alumina.

[0028] Example 3 A preparation method of mesoporous ultrastable alumina, comprising the following steps: S1: Mix aluminum hydroxide powder and a sodium hydroxide solution with a concentration of 3.8 mol / L evenly (the molar ratio of aluminum hydroxide powder to sodium hydroxide in the sodium hydroxide solution is 1:3.4), pressurize to 0.35 MPa, heat up to 128 °C, and react for 5.3 h to obtain a sodium aluminate solution; S2: Mix a part of the sodium aluminate solution prepared in step S1 and an aluminum sulfate solution with a concentration of 0.31 mol / L at a volume ratio of 1.4:1, stir and heat up to 58 °C, add the sodium aluminate solution to control the pH value of the reaction system to 8.1 until the reaction is complete, continue to heat up to 90 °C, carry out the crystallization reaction for 26 h, then add sodium silicate (the molar mass of sodium silicate is 0.7% of the total molar mass of aluminum in the sodium aluminate solution and the aluminum sulfate solution), continue to react for 2.3 h, stand and cool, filter, wash with deionized water until there is no sulfate ion in the washing solution, dry, and grind to obtain a powdery material; S3: Heat the powdery material obtained in step S2 to 825 °C at a rate of 26 °C / min and calcine for 4.6 h, then cool to 25 °C at a cooling rate of 45 °C / min to obtain modified alumina powder; S4: Add the modified alumina powder prepared in step S3 and hexamethyldisilazane to an aluminum sulfate solution with a concentration of 0.3 mol / L at a mass ratio of 12:1, heat up to 53 °C, and dropwise add the sodium aluminate solution prepared in step S1 (the volume ratio of the sodium aluminate solution to the aluminum sulfate solution is 1.4:1, and the mass ratio of the modified alumina powder to sodium aluminate in the sodium aluminate solution is 9:2) under stirring. Add sodium carbonate to control the pH value of the reaction system to 9.8 until the reaction is complete, continue to heat up to 145 °C, carry out the crystallization reaction for 23 h, cool, filter, wash, dry, and grind to obtain mesoporous ultrastable alumina.

[0029] Comparative Example 1 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, the pH value of the reaction system is controlled to be 9.0.

[0030] Comparative Example 2 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, the temperature of the crystallization reaction is 140 °C.

[0031] Comparative Example 3 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, an equal amount of deionized water is used to replace sodium silicate.

[0032] Comparative Example 4 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S2 of this comparative example, the molar mass of sodium silicate is 1.5% of the total molar mass of aluminum in the sodium aluminate solution and the aluminum sulfate solution.

[0033] Comparative Example 5 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S3 of this comparative example, the calcination temperature is 1300 °C.

[0034] Comparative Example 6 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S4 of this comparative example, the pH value of the reaction system is 8.5.

[0035] Comparative Example 7 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S4 of this comparative example, the temperature of the crystallization reaction is 200 °C.

[0036] Comparative Example 8 The preparation method of alumina described in this comparative example is similar to that of Example 3. The difference between this comparative example and Example 3 is that in step S4 of this comparative example, hexamethyldisilazane is not added.

[0037] Test Example Test samples: Alumina prepared in Examples 1 - 3 and Comparative Examples 1 - 8; Test method: The specific surface area and pore volume of the test samples before thermal aging and after 4-hour high-temperature aging at 1200 °C were measured by the BET method. Specifically, degassing was carried out under vacuum conditions at 300 °C for 8 - 12 hours, and the vacuum degree of the degassing station should reach below 45 mTorr. After degassing, isothermal adsorption / desorption was carried out at 77.8 K. The specific surface area of the sample was obtained according to the BET formula; when the relative pressure P / P0 reached the maximum, the volume of nitrogen adsorbed by the sample at this time was recorded, and thus the pore volume of the sample could be obtained.

[0038] Test results: See Table 1.

[0039] Table 1

[0040] As can be seen from Table 1, the mesoporous ultra-stable alumina prepared in Examples 1 - 3 of the present invention has a relatively large pore volume and specific surface area, and the changes in specific surface area and pore volume after thermal aging are relatively small. This shows that the mesoporous ultra-stable alumina provided by the present invention has a good pore structure, good high-temperature stability, and still has good loading performance after high-temperature aging.

[0041] Compared with Example 3, in Comparative Example 1, the pH value of the reaction system in Step S2 was changed, and in Comparative Example 2, the crystallization reaction temperature in Step S2 was changed. However, the specific surface area and pore volume of the prepared alumina decreased to a certain extent. This indicates that the pH value of the reaction system and the crystallization reaction temperature are one of the key factors for adjusting the pore structure of alumina. When the pH value of the reaction system increases, the crystallinity of pseudo-boehmite increases and the particle size becomes larger, resulting in a decrease in the specific surface area. The pore volume first increases with the increase in crystallinity, but as the pH value continues to increase, the crystal nuclei undergo a dissolution-reformation process in the solution system, leading to a decrease in the pore volume. The increase in the crystallization reaction temperature promotes the increase in the crystallinity of pseudo-boehmite, but reduces the uniformity of the pore size distribution, resulting in a decrease in the specific surface area. In Comparative Example 3, sodium silicate was not added in Step S2, in Comparative Example 4, the addition amount of sodium silicate in Step S2 was changed, and in Comparative Example 8, hexamethyldisilazane was not added in Step S4. However, the specific surface area and pore diameter of the alumina after high-temperature aging decreased. This shows that the addition of sodium silicate and hexamethyldisilazane can effectively improve the high-temperature stability of the pore structure of alumina, and excessive sodium silicate will cause the pore channels of alumina to be blocked, thereby reducing the specific surface area and pore volume. In Comparative Example 5, the calcination temperature in Step S3 was changed, but the specific surface area and pore volume of the prepared alumina decreased. This indicates that after exceeding the calcination temperature provided by the present invention, the pore channels of alumina will collapse, resulting in pore blockage, thereby reducing the specific surface area and pore volume. In Comparative Example 6, the pH value of the reaction system in Step S4 was changed, and in Comparative Example 7, the crystallization reaction temperature in Step S4 was changed. However, the specific surface area and pore volume of the prepared alumina after high-temperature aging decreased slightly. This shows that the pseudo-boehmite prepared in Step S4 of the present invention can provide a certain support for the pore structure of alumina and improve the high-temperature resistance of alumina.

[0042] The above embodiments are merely illustrative of the present invention and do not limit the present invention. Those skilled in the art shall not modify the above embodiments without departing from the spirit and scope of the present invention. All equivalent modifications or changes made by those with ordinary knowledge in the technical field without departing from the technical idea of the present invention still fall within the protection scope of the present invention.

Claims

1. A method for preparing mesoporous ultrastable alumina, characterized in that: The following steps are involved: S1: mixing aluminum hydroxide powder and sodium hydroxide solution evenly and reacting for 5-6 hours to obtain sodium aluminate solution; S2: mixing the sodium aluminate solution obtained in step S1 with the aluminum sulfate solution, stirring and heating, adding the sodium aluminate solution to control the pH value of the reaction system to 7.8-8.3 until the reaction is completed, continuing to heat the reaction for crystallization, then adding sodium silicate, continuing the reaction, standing and cooling, filtering, washing, drying, grinding, and obtaining a powdery material; S3: calcining the powdery material obtained in step S2, and obtaining modified alumina powder after cooling; S4: Add the modified alumina powder and hexamethyldisilazane obtained in step S3 to the aluminum sulfate solution, increase the temperature, add the sodium aluminate solution obtained in step S1 dropwise under stirring, add sodium carbonate to control the pH value of the reaction system to 9.7-10.0 until the reaction is completed, continue to increase the temperature for crystallization reaction, filter after cooling, wash, dry and grind to obtain mesoporous ultra-stable alumina.

2. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: The molar ratio of the aluminum hydroxide powder to the sodium hydroxide in the sodium hydroxide solution in step S1 is 1:3.2-3.5; the concentration of the sodium hydroxide solution is 3.5-4 mol / L.

3. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: The reaction temperature in step S1 is 125-130° C., and the reaction pressure is 0.3-0.4 MPa.

4. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: In step S2, the volume ratio of the sodium aluminate solution to the aluminum sulfate solution is 1.2-1.5:1; the concentration of the aluminum sulfate solution is 0.2-0.4 mol / L; the stirring and heating temperature is 55-60° C., and the reaction time is 2-2.5 hours.

5. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: The temperature of the crystallization reaction in step S2 is 85-95° C., and the time of the crystallization reaction is 24-30 hours.

6. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: The molar mass of the sodium silicate in step S2 is 0.5%-0.8% of the total molar mass of aluminum in the sodium metaaluminate solution and the aluminum sulfate solution.

7. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: In step S3, the calcination temperature is 820-830°C, the calcination time is 4-5h, the calcination heating rate is 20-30°C / min; and the cooling rate is 40-50°C / min.

8. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: In step S4, the volume ratio of the aluminum sulfate solution to the sodium aluminate solution is 1:1.2-1.5; the concentration of the aluminum sulfate solution is 0.2-0.4 mol / L.

9. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: In step S4, the mass ratio of the modified alumina powder to hexamethyldisilazane is 10-13:1; the mass ratio of the modified alumina powder to sodium aluminate in the sodium aluminate solution is 7-10:2-3.

10. The method for preparing mesoporous ultrastable alumina according to claim 1, characterized in that: The temperature of the heating in step S4 is 50-55° C.; the temperature of the crystallization reaction is 140-150° C., and the time of the crystallization reaction is 20-24 hours.

Citation Information

Patent Citations

  • Macroporous boehmite with large specific surface area and preparation method thereof

    CN115594207A

  • Preparation method of high temperature-resistant alumina aerogel material

    CN103342537A

  • Preparation method of high-temperature-resistant block alumina aerogel

    CN109250738A

  • Preparation method of macroporous activated alumina powder

    CN112794351A

  • Porous alumina matrix with high hydrothermal stability and preparation method thereof

    CN113860344A

Cited By

  • Synthetic method of modified aluminum oxide

    CN121317835A